(untitled) (Práxis Educativa, 2020)
The present paper aims to analyze the changes that the "new right-wing" promotes in Uruguay in the field of education around three central themes: a) the concept or nature of education, b) the organization and administration of Basic Education, and c) the work and participation of teachers. To this end, the main achievements, strengths, and tensions that the cycle of progressive governments in Uruguay displayed in the field of education are recovered, while the central aspects of the conservative education project that the new right-wing government is promoting in the country are analyzed. The analysis carried out allows to allude to the transition from latent privatization to manifest privatization present in the political strategy that materializes in the “Proyecto de Ley de Urgente Consideración” (Bill of Urgent Consideration), in the framework of which forms of privatization in and of education are promoted that weaken its place as a public space. Keywords: Conservative project. Privatization of education. Basic Education.